Disparate Effects of Repeated Testing: Reconciling Ballard's (1913) and Bartlett's (1932) Results - Wheeler, Mark A.; Roediger, Henry L. (Psychological Science, 1992)
Bartlett (1932) gave subjects a prose passage and showed how recall dropped when they were tested repeatedly. Ballard (1913), using poetry, and Erdelyi and Becker (1974), using pictures, reported improvements in performance (or hypermnesia) over repeated testing. We investigated two likely factors leading to the discrepant results: the type of material and the interval between tests. The primary cause of the differing outcomes is the interval between tests. In general, when the intervals between successive tests are short improvement occurs between tests. When these intervals are long, forgetting occurs. The type of material used plays little role: Hypermnesia in recall of prose (even “The War of the Ghosts”) occurred with short intervals between tests. We also report a striking confirmation of the power of tests to enhance memory: Repeated tests shortly after study greatly improved recall a week later.